2019
DOI: 10.7567/1347-4065/ab0d0a
|View full text |Cite
|
Sign up to set email alerts
|

Observation of dislocations and their arrays in physical vapor transport-grown AlN single-crystal substrate by synchrotron X-ray topography

Abstract: Dislocations in a single-crystal aluminum nitride bulk substrate have been characterized using synchrotron X-ray topography (XRT). Threading edge dislocations (TEDs) and screw-type dislocations as well as {0001}-plane basal plane dislocations have been observed, and their Burgers vectors were evaluated based on the XRT contrast of these dislocations. Particular attention has been paid to the direction of the Burgers vectors of dislocation arrays composed of TEDs. By analyzing the bright/dark contrast change of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…[4][5][6][7] Dislocations can be imaged, e.g., by transmission electron microscopy (TEM) or X-ray topography (XRT). [4,[8][9][10][11] However, both methods are based on expensive equipment and require sophisticated analysis. Furthermore, TEM requires considerable sample preparation and the investigation is confined to small areas, while XRT is only usable if the dislocation densities are below 10 6 cm À2 .…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Dislocations can be imaged, e.g., by transmission electron microscopy (TEM) or X-ray topography (XRT). [4,[8][9][10][11] However, both methods are based on expensive equipment and require sophisticated analysis. Furthermore, TEM requires considerable sample preparation and the investigation is confined to small areas, while XRT is only usable if the dislocation densities are below 10 6 cm À2 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the dislocations are most likely BPDs. While the Burgers vector of BPDs connecting threading dislocations has been identified as being of type 1 3 h2110i, these seem to appear arc shaped or as half loops instead (Yao et al, 2019). BPDs looking similar to those shown in Fig.…”
Section: Resultsmentioning
confidence: 69%
“…6(b)-6(d) must be basal plane screw dislocations (BPSs) of type b ¼ l ¼ 1 3 h2110i. To our knowledge, this specific dislocation type has been distinctively identified only once and very recently in PVTgrown AlN material (Yao et al, 2019). The research group suggests thermal stress as the likely cause, indicated by the increased density of the BPSs near the edge of the wafer.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…In general, spatial distributions of dislocations in AlN crystals with densities below 10 6 cm –2 can be studied by defect-selective etching (DSE), ,, laser scattering tomography (LST), and X-ray diffraction imaging techniques such as X-ray topography (XRT). …”
Section: Introductionmentioning
confidence: 99%